2022
DOI: 10.1108/jhom-11-2021-0425
|View full text |Cite
|
Sign up to set email alerts
|

Causes, impacts and possible mitigation of non-attendance of appointments within the National Health Service: a literature review

Abstract: PurposeMissed appointments within the National Health Service (NHS) are a drain on resources, associated with not only considerable time and cost implications, but also sub-optimal health outcomes. This literature review aims to explore non-attendance within the NHS in relation to causes, impacts and possible mitigation of negative effects of missed appointments.Design/methodology/approachMEDLINE, CINAHL Plus and PubMed were searched with a date range of 2016–2021. Databases were searched for peer-reviewed art… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 51 publications
(363 reference statements)
0
14
0
Order By: Relevance
“…Missed appointments result in delays in care, inefficient resource use, and worse health outcomes (1)(2)(3), particularly in patients with poorer health and more complex social needs (4)(5)(6). The association between missed appointments and health inequalities is well established (2,7).…”
Section: Introductionmentioning
confidence: 99%
“…Missed appointments result in delays in care, inefficient resource use, and worse health outcomes (1)(2)(3), particularly in patients with poorer health and more complex social needs (4)(5)(6). The association between missed appointments and health inequalities is well established (2,7).…”
Section: Introductionmentioning
confidence: 99%
“…1 In 2019/2020, there were 5 656 365 outpatient no-shows across the National Health Service (NHS) in the United Kingdom, 2 with an estimated annual cost as high as £750 million. 3 Outpatient no-shows are associated with worse health outcomes 4 and are an independent predictor of increased subsequent acute care utilization. 5,6 Outpatient no-shows are a complex, multifactorial phenomenon, associated with patient characteristics, including demographics relevant to equity (eg, receipt of welfare payments, travel time to appointment) and characteristics of the appointment and the healthcare system (eg, lead time).…”
Section: Introductionmentioning
confidence: 99%
“…5,6 Outpatient no-shows are a complex, multifactorial phenomenon, associated with patient characteristics, including demographics relevant to equity (eg, receipt of welfare payments, travel time to appointment) and characteristics of the appointment and the healthcare system (eg, lead time). 1,4,7,8 Organizational interventions, such as overbooking, and interventions facilitating access to appointments, such as reminders, [9][10][11][12][13] transportation to appointments, and financial incentives, 14 have been developed to increase attendance, reduce noshows, or increase timely cancelations and reschedules. These goals are distinct, and preference for one over the other may depend on the clinical context.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Research has indicated major predictors of first appointment non-attendance can include clients with a lower non-risk score on the CORE-34 (Evans et al , 2000), regular thoughts of “being better off dead” (as indicated on the CORE-34; Evans et al ) or recent onset of a mental health difficulty (one month or less) or long-term condition (more than two years; Di Bona et al , 2014). Clients from lower socioeconomic backgrounds and those with multiple co-morbidities are also reportedly more likely to miss appointments, often citing forgetfulness, transportation difficulties and family commitments (Wilson and Winnard, 2022). Conversely, clients found to most likely attend their first appointment included those who self-referred and those with fewer previous referrals (Davis et al , 2020).…”
Section: Introductionmentioning
confidence: 99%